Stormwater characterisation and modelling for Sungai Air Hitam in Selangor, Malaysia using model for urban stormwater improvement conceptualisation (music) - Noorhayati, Idros; Lariyah, Mohd Sidek; Nur Anis, Aishah M. Rahim; Nurshahira, Mohd Noh; Abdelkader, Amr M.; Hairun, Aishah Mohiyaden; Hidayah, Basri; Mohd Hafiz, Bin Zawawi; Ali, Najah Ahmed * (Elsevier, 2024)
The aim of this study is to evaluate the current water quality status of one of the urban rivers in Malaysia, called Sungai Air Hitam. The river's water supply is not only unsuitable for the inhabitants but also hazardous to the aquatic species that depend on it. In order to simulate the water quality formulation of the river, the Model for Urban Stormwater Improvement Conceptualization (MUSIC) was used. The effects of various best management practices (BMPs) components have been examined to improve the river's water quality. This study also investigated different scenarios of the expected future changes in the land cover and the quality of the river. As the proportion of impervious surfaces increases, the urban hydrology cycle can be significantly altered, resulting in an increase in volumes and peak flows, and a decrease in storage, infiltration, and interception. The MUSIC results have shown significant reductions in biochemical oxygen demand (BOD), total suspended solids (TSS), total phosphorus (TP), and total nitrogen (TN) after introducing BMPs. It was also noticed that the prediction of pollutants falls within the acceptable range set by the Urban Stormwater Management Manual for Malaysia (MSMA) 2nd edition. For the land cover, it was found that the total reduction of BOD, TSS, TP, and TN for existing land use is 92.5 %, 94.5 %, 90.7 % and 91.9 %. Meanwhile, the total reduction in future land use is 81.6 % for BOD, 86.2 % for TSS, 80.9 % for TP and 80.8 % for TN. From the simulation results, it was observed that the application of BMPs has successfully reduced the observed mean BOD concentration from 92.38 mg/L (Class V) to 6.93 mg/L (Class IV) of the national water quality standards, NWQS, water quality index. As a result, the water quality index of the overall catchment has improved from Class IV to Class III (WQ1, WQ3, and WQ4) and from Class V to IV (WQ2) with the application of the BMPs. This assessment aims to raise awareness within the Sungai Air Hitam community regarding the importance of preserving river cleanliness and understanding the long-term environmental impact of water quality. These findings underscore the importance of an integrated system in managing urban water systems, which can offer valuable insight to the decision-makers.